An Accuracy Analysis of Translation in English-Indonesian Bilingual Children’s Storybooks through Back-Translation - Yeni Erlita; Berlin Sibarani; Juli Rachmadani Hasibuan; Johannes Jefria Gultom (Jambura Journal of English Teaching and Literature, 2026)
This study evaluates the translation accuracy of the English-Indonesian bilingual children’s storybook Purple and Walter: Save the Trees using the Back-Translation method to ensure its reliability for bilingual education. Employing a qualitative descriptive design with textual analysis, the research analyzed 65 linguistic units comprising sentences and dialogue segments following the four-step "circular" validation procedure (Forward Translation, Review, Blind Back-Translation, and Comparison) proposed by Yu et al. (2003). The data were further assessed using Nababan’s (2012) translation accuracy framework. The findings indicate a high level of semantic consistency, with 0% (0 units) falling into Low Accuracy, 27.7% (18 units) categorized as Moderate Accuracy, 52.3% (34 units) as High Accuracy, and 20.0% (13 units) as Very High Accuracy. Results demonstrate that while the core message and narrative function remain stable (72.3% total High/Very High accuracy), Moderate Accuracy units reveal a consistent pattern of stylistic reduction, where descriptive intensity and double emphasis (e.g., "tiny little") are simplified for audience adaptation. This study concludes that the Back-Translation method serves as a rigorous "diagnostic filter" for detecting subtle meaning shifts that traditional direct comparisons may overlook. The high semantic reliability of the text confirms its effectiveness for literacy development, though a balance between readability and the preservation of stylistic richness is recommended for future bilingual materials.